Approach for assessing coastal vulnerability to oil spills for prevention and readiness using GIS and the Blowout and Spill Occurrence Model. (August 2015) - Nelson, J.R.; Grubesic, T.H.; Sim, L.; Rose, K.; Graham, J.
Abstract: Increasing interest in offshore hydrocarbon exploration has pushed the operational fronts associated with exploration efforts further offshore into deeper waters and more uncertain subsurface settings. This has become particularly common in the U.S. Gulf of Mexico. In this study we develop a spatial vulnerability approach and example assessment to support future spill prevention and improve future response readiness. This effort, which is part of a larger integrated assessment modeling spill prevention effort, incorporated economic and environmental data, and utilized a novel new oil spill simulation model from the U.S. Department of Energy's National Energy Technology Laboratory, the Blowout and Spill Occurrence Model (BLOSOM). Specifically, this study demonstrated a novel approach to evaluate potential impacts of hypothetical spill simulations at varying depths and locations in the northern Gulf of Mexico. The simulations are analyzed to assess spatial and temporal trends associated with the oil spill. The approach itself demonstrates how these data, tools and techniques can be used to evaluate potential spatial vulnerability of Gulf communities for various spill scenarios. Results of the hypothetical scenarios evaluated in this study suggest that under conditions like those simulated, a strong westward push by ocean currents and tides may increase the impacts of deep water spills along the Texas coastline, amplifying the vulnerability of communities on the local barrier islands. Ultimately, this approach can be used further to assess a range of conditions and scenarios to better understand potential risks and improve informed decision making for operators, responders, and a of stakeholders to support spill prevention as well as response readiness. Highlights: We estimate vulnerability using GIS and simulated offshore oil spill trajectories. Findings suggest a strong westward movement during March and April. Approach demonstrates enhanced effectiveness in spatial vulnerability assessments. Results enhance understanding of oil spill behavior in Gulf of Mexico. Different spatial extents result from varying the location and depth of blowout.